Comparison of the virulence and transmissibility of canine H3N2 influenza viruses and characterization of their canine adaptation factors - Lee, In-Won (Emerg Microbes Infect, 2018)
Recent canine influenza outbreaks have raised concerns about the generation of pathogenic variants that may pose a threat to public health. Here, we examine avian-like H3N2 canine influenza viruses (CIVs) isolated from 2009 to 2013 in South Korea from dogs. Phylogenetic analysis revealed that these viruses are closely related to strains previously isolated from dogs in Korea and China. However, molecular characterization demonstrated non-synonymous mutations between the canine viruses, particularly in the putative H3 antigenic sites, NA stalk regions, and in the internal genes of the 2012–2013 isolates compared with the 2009 isolate. Animal experiments showed that three representative isolates (A/canine/Korea/AS-01/2009(AS-01/09), A/canine/Korea/AS-05/2012(AS-05/12) and A/canine/Korea/AS-11/2013(AS-11/13), were readily droplet transmitted between dogs, whereas AS-05/12 induced more severe clinical disease and was lethal in dogs compared with AS-01/09. Although all viruses were able to infect ferrets, AS-05/12 consistently yielded higher nasal wash titers and was transmissible to ferrets via airborne droplets. Using reverse genetics, we show that the NA, NP, and M genes of CIV are critical for the adaptation of avian H3N2 viruses, and the resulting reassortant genotypes promote viral growth in dogs in a manner similar to that of the wild-type AS-01/09 virus. Taken together, these results demonstrate that CIVs continuously evolve in dogs thereby allowing them to gain a foothold in mammalian hosts. Importantly, we elucidated the genetic contributions of the NA, NP, and M genes to the adaptability of CIVs derived from the avian H3N2 virus.